Vaccines targeting Staphylococcus aureus skin and bloodstream infections require different composition - Luna, Brian M. (PLoS One, 2019)
Staphylococcus aureus infections represent a major public health threat, but previous attempts at developing a universal vaccine have been unsuccessful. We attempted to identify a vaccine that would be protective against both skin/soft tissue and bloodstream infections. We first tested a panel of staphylococcal antigens that are conserved across strains, combined with aluminum hydroxide as an adjuvant, for their ability to induce protective immunity in both skin and bacteremia infection models. Antigens were identified that reduced dermonecrosis during skin infection, and other non-overlapping antigens were identified that showed trends to protection in the bacteremia model. However, individual antigens were not identified that mediated substantial protection in both the skin and bacteremia infection models. We therefore tested a variety of combinations of proteins to seek a single combination that could mediate protection in both models. After iterative testing, a vaccine consisting of 3 antigens, ABC transporter protein (SACOL2451), ABC2 transporter protein (SACOL0695), and α-hemolysin (SACOL1173), was identified as the most effective combination. This combination vaccine provided protection in a skin infection model. However, these antigens were only partially protective in the bacteremia infection model. Even by testing multiple different adjuvants, optimized efficacy in the skin infection model did not translate into efficacy in the bacteremia model. Thus protective vaccines against skin/soft tissue infections may not enable effective protection against bloodstream infections.